Identifying risk factors for neonatal hypoglycemia in infants conceived through assisted reproductive technology: A retrospective cohort study - Nurgaliyeva, Zhanar; Ilmuratova, Sevara; Lokshin, Vyacheslav; Manzhuova, Lyazzat; Seisebayeva, Roza (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: 12 million infants are born worldwide after assisted reproductive technologies (ART), yet their health remains under-researched. Evidence indicates that neonatal hypoglycemia (NG) is more prevalent in ART-conceived infants. This study aims to identify risk factors for NG and explore prediction possibilities in this population, focusing specifically on ART-conceived infants without direct comparison to naturally conceived infants. Research design and Methods: Our retrospective cohort study involved 120 infants born after ART. The participants met specific criteria, including being born from a successful ART program resulting in single or multiple pregnancies. Those born using donor oocytes/sperm, intrauterine insemination, or surrogacy were not included. Data for the anamnesis were gathered and analyzed using IBM SPSS Statistics 26. Results: ART-conceived infants were at greater risk of being born with NG in cases of multiple pregnancies (OR=14.2; 95% CI: 1.71-117.67), isthmic-cervical insufficiency (OR=10.29; 95% CI: 1.47-71.98), premature birth (OR=13.39; 95% CI: 2.61-68.84), and uterine infertility (OR=10.29; 95% CI: 1.47-71.98). ART-conceived infants had a higher incidence of NG when they were late preterm (OR=16.95; 95% CI: 3.26-88), with fetal growth restriction (OR=13.38; 95% CI: 2.42-73.8), infantile asphyxia (OR=45; 95% CI: 7.86-257.64), congenital pneumonia (OR=16.96; 95% CI: 3.45-83.3), congenital infection (OR=18; 95% CI: 2.98-108.8), respiratory distress syndrome (OR=16.09; 95% CI: 3.6-72.03), and low or very low birth weight. A regression model that exhibited statistical significance encompassed late prematurity, neonatal asphyxia, congenital infection, and maternal hormone intake before pregnancy. Conclusions: Our study on ART-conceived infants identified key risk factors for NG. The prognostic model we developed supports early intervention and preventive measures, enhancing care for these infants. Future studies should include a control group of naturally conceived infants to compare the risk of NG between ART-conceived and naturally conceived populations.